Implementasi Manajemen Pemasaran Pendidikan dalam Meningkatkan Minat Peserta Didik Baru: (Studi Kasus di MTs Negeri 3 Bekasi) - Muhamad Ihsan Khuluki; Eva Athifah; Beta Hikmah Zahrotunnisa; Lu'lu Atun Naafi'ah; Farchatul Maru’ah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study aims to analyze the implementation of educational marketing management in increasing the interest of new students at MTs Negeri 3 Bekasi City, with a focus on the application of the POAC management functions (Planning, Organizing, Actuating, Controlling). The study employs a descriptive qualitative approach using a case study design. Primary data were obtained through observation and in-depth interviews with the Madrasah Principal and the Vice Principal for Student Affairs, who serves as the Chair of the PMBM Committee, while secondary data were sourced from relevant journals and literature. The research results indicate that marketing planning was carried out systematically through the formation of the PMBM committee, academic, religious, and Quranic literacy selection processes, as well as the utilization of digital and print media. Organization involved all school components in a structured manner, while promotional activities highlighted students’ academic, non-academic, and moral achievements through social media and word of mouth. This strategy proved effective, as evidenced by the number of applicants far exceeding the admission quota. However, implementation still faces challenges related to funding, limited land availability, and public perceptions regarding the difficulty of the selection process, which are addressed through routine evaluations and collaboration with government agencies.